Switchable square ring bandpass to bandstop filter for ultra-wideband applications. Issue 1 (14th October 2015) - Alqaisy, Mushtaq; Chakrabraty, Chandan K.; Ali, Jawad K.; Alhawari, Adam Reda; Saeidi, Tale
Abstract : In this manuscript, serial-shunt of square ring resonators with step-impedance open circuited stub resonators to produce a new on-off switchable bandpass to bandstop response in the same ultra-wideband microstrip filter structure is proposed. The closed ring of series-shunt square ring resonators with a combine stubs are introduced to excite the bandpass response while bandstop characteristic excited when gaps are embedded in the corners of the square ring resonators. The main advantage of this microstrip filter is its capability to switch from bandpass-to-bandstop operation using open-short gap, respectively. A microwave simulator is utilized to show the switchable case by replacing Skyworks radio frequency diodes (RF-PIN) instead of those gaps. The entire filter models have been simulated using the computer simulation technology (CST) Microwave Studio. The computed results for the proposed filters were compared with the measured results of the both prototype structures (bandpass- and bandstop-filter). The codes also showed good agreement between them. Other advantages include being small in size, and low in effective cost.